8 - Governing ‘Ethnicised’ Public Sphere: Insights from Nigeria: https://doi.org/10.4314/ad.v35i4.70221 - Orji, Nkwachukwu (Africa Development, 2021)
This article explores the way in which ethnically diverse societies govern their public sphere. It shows that the public sphere in multiethnic societies is an arena of conflict where cultural and ideological contest or negotiation among a variety of groups takes place. Drawing from Nigeria’s experience, the article examines the conflict management arrangement devised to regulate hostile inter-group relations in the public sphere. It identifies power-sharing as the most fundamental conflict management strategy adopted to govern Nigeria’s public sphere. The article argues that although power-sharing features as the most acceptable modality for moderating inter-group conflicts in Nigeria, its usefulness is limited by the fact that it widens the asymmetrical and oligarchic power of the dominant groups and hampers the growth of democracy.